2021
DOI: 10.1136/jnnp-2020-325580
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural plasticity in nociceptive pathways after spinal cord injury

Abstract: ObjectiveTo track the interplay between (micro-) structural changes along the trajectories of nociceptive pathways and its relation to the presence and intensity of neuropathic pain (NP) after spinal cord injury (SCI).MethodsA quantitative neuroimaging approach employing a multiparametric mapping protocol was used, providing indirect measures of myelination (via contrasts such as magnetisation transfer (MT) saturation, longitudinal relaxation (R1)) and iron content (via effective transverse relaxation rate (R2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Our study demonstrated gray matter atrophy in the bilateral thalamus, which was in accordance with previous VBM studies and meta-analyses ( 23 , 34 36 ). Although neurons in the brain are not disrupted directly following SCI, the afferent motor pathway and efferent sensory pathway undergo degenerative processes ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our study demonstrated gray matter atrophy in the bilateral thalamus, which was in accordance with previous VBM studies and meta-analyses ( 23 , 34 36 ). Although neurons in the brain are not disrupted directly following SCI, the afferent motor pathway and efferent sensory pathway undergo degenerative processes ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…The putamen, a part of the striatum and basal ganglia, is involved with production of movement, reward, and multisensory integration of noxious and non-noxious stimuli, with previously demonstrated pain-related activation hypothesized to be involved in motor responses for withdrawal from painful stimuli or inhibition of painful movement ( Bingel et al, 2002 , Borsook et al, 2010 , Chudler and Dong, 1995 ). Alterations in R2* signal, reflective of iron content, in the parahippocampal gyrus and basal ganglia were previously identified in individuals with SCI with neuropathic pain ( Kyathanahally et al, 2021 ), which demonstrates overlap with our identified alterations in the BOLD signal between the parahippocampal gyrus and putamen. A previously identified negative correlation between neuropathic pain severity in individuals with SCI and mean diffusivity of the amygdala suggest microstructural changes could contribute to our findings of altered amygdala connectivity ( Gustin et al, 2014 ).…”
Section: Discussionsupporting
confidence: 80%
“… Lee et al, 2022 , Min et al, 2015 , Seixas et al, 2016 , Sprenger et al, 2015 ), putamen ( Iwabuchi et al, 2023 ; B. Lee et al, 2022 , Min et al, 2015 , Ruscheweyh et al, 2018 , Sprenger et al, 2015 , Zhang et al, 2014 ), and the periaqueductal gray matter ( Kyathanahally et al, 2021 , Li et al, 2020a , Linnman et al, 2012 , Sprenger et al, 2015 ) ( Supplemental Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower MT values within the dorsal columns and spinothalamic tracts are also related to lower light touch and pin-prick scores in chronic SCI, respectively, highlighting the association between remote tract demyelination and specific sensory impairments [44 ▪ ]. Additionally, in terms of microstructural measures revealed by qMRI, higher iron-sensitive R2 ∗ values can also be detected along nociceptive pathways in the cervical cord of chronic SCI patients with NP; its magnitude being associated with pain intensity [45].…”
Section: Remote Spinal Cord Mri Biomarkers Of Spinal Cord Injury Seve...mentioning
confidence: 92%